SEMINAR STRATEGI PERENCANAAN KEUANGAN MENGHADAPI KETIDAKPASTIAN GEOPOLITIK - Widayanti, Asti; Satria, Dy Ilham; Anindya, Desy Astrid; Pardede, Mazmur; Winarningsih, Srihadi; Zarkasyi, Wahyudin; Sukmadilaga, Citra (LPPM Universitas Bina Bangsa, 2025)
This seminar aims to provide literacy and education on the considerations in financial strategy planning amidst geopolitical uncertainty issues. The seminar was conducted with presentations and discussions from speakers representing the perspectives of academia, government, and companies. The feedback and evaluation process measures satisfaction with the material, speakers, and event organization. The results show that there are 410 participants, with 50.2% being students. From the presentation, it was conveyed that geopolitical uncertainty impacts economic development, trade, and investment, regulatory improvements, and strengthening economic resilience through diversification, reform, digitalization, and capital development. Financial planning strategies are carried out by implementing digital transformation, portfolio diversification, and cost efficiency by observing market trends and stakeholder opinions. The evaluation results show that 83% of participants agree that the seminar activities have provided literacy on financial planning strategies.